2009
DOI: 10.1016/j.cma.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive anisotropic meshing for steady convection-dominated problems

Abstract: Obtaining accurate solutions for convection-diffusion equations is challenging due to the presence of layers when convection dominates the diffusion. To solve this problem, we design an adaptive meshing algorithm which optimizes the alignment of anisotropic meshes with the numerical solution. Three main ingredients are used. First, the streamline upwind Petrov-Galerkin method is used to produce a stabilized solution. Second, an adapted metric tensor is computed from the approximate solution. Third, optimized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…A similar recipe is used in [4], where an SUPG method for the Stokes equations is employed. This choice leads to a stabilization matrix ‚ K in (4), which takes into account the solution anisotropy.…”
Section: An Anisotropic Recovery-based Error Estimatormentioning
confidence: 99%
See 3 more Smart Citations
“…A similar recipe is used in [4], where an SUPG method for the Stokes equations is employed. This choice leads to a stabilization matrix ‚ K in (4), which takes into account the solution anisotropy.…”
Section: An Anisotropic Recovery-based Error Estimatormentioning
confidence: 99%
“…When moving from time t s to the next one t sC1 , we first compute an intermediate solution Q h is used to linearize system (4). Also, in this case, we set a sort of iterative procedure.…”
Section: The Unsteady Casementioning
confidence: 99%
See 2 more Smart Citations
“…point distributions with special properties such as high aspect ratio spacings that would be useful for resolving boundary layers. Such an adaptive anisotropic meshing scheme for solving two-dimensional steady convection-dominated problems was developed in [94], in particular, the meshes are generated by the ACVDT algorithm [46] in combination with metric tensor information at each level of refinement. Some preliminary results have shown that the adaptive ASCVT approach results in substantial improvements compared to using regular isotropic CVT meshes; see Figure 11 for an illustration.…”
Section: Cvt-based Adaptive Algorithms For Numerical Pdesmentioning
confidence: 99%